Investors' Fear and Herding in the Johannesburg Stock Exchange (JSE) - Patel, Zubair (School of Economics, 2021)
Investors herd when they follow the investment decisions of other market participants and ignore their own private information, causing asset valuations to deviate from their fundamentals. This paper examines herding in the South African equity market by examining the impact of investor fear on herding behavior, using a survivorship-bias free daily dataset of companies within the JSE All Share Index over the period: 3 May 2002 to 31 December 2019. Using the cross-sectional absolute deviation (CSAD), this study examines market-wide herding behavior over multiple sub-periods, which consists of before, during and after the global financial crisis of 2007/08. The results suggest no evidence of herding towards the market return; on the contrary there is evidence of ‘anti-herding' behaviour during periods of market stress. However, there is significant herding towards the domestic fear index, which becomes more pronounced during the crisis period. Furthermore, investor herd behaviour appears to be sensitive to spill-over effects from the US investor fear-gauge, suggesting interconnectedness with global financial markets. Therefore, these findings suggest that fear plays an important role in enforcing irrational behaviour.